Perbedaan Tarif Pajak Badan: Apakah Perusahaan Masih Melakukan Praktik Penghindaran Pajak? - Pramiana, Omi; Salsabila, Nadia (INVENTORY: JURNAL AKUNTANSI, 2024)
This study aims to determine differences in tax avoidance practices in companies listed on the IDX before and after differences in tax rates. The method used in this research is quantitative. This study uses secondary data that comes from the IDX website for a period of 1 year before the difference in tax rates and 1 year after the difference in tax rates. The data analysis technique used the different test (paired sample t-test) and the Wilcoxon signed ranks test using the SPSS Version 20 application. The results of the analysis showed that there were significant differences in tax avoidance practices before and after differences in tax rates in the primary consumer goods and financial sectors. Meanwhile, in the energy, raw goods, industry, health, infrastructure, non-primary consumer goods, technology, property and real estate and then transportation and logistics sectors, there were no significant differences in the practice of tax avoidance. This research is able to contribute to companies (corporate taxpayers), society, investors, government and future researchers.